2015
DOI: 10.1007/s13277-015-4228-y
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic regulation and anti-tumorigenic effects of SH2-containing protein tyrosine phosphatase 1 (SHP1) in human gastric cancer cells

Abstract: SH2-containing protein tyrosine phosphatase 1 (SHP1) is an important negative regulator in cytokine-mediated signal transduction and cell cycling. Recent studies have demonstrated that SHP1 promoter methylation is frequently observed in gastric adenocarcinoma tissues. In this in vitro study, we attempted to reveal promoter hypermethylation and to investigate effects of SHP1 in gastric carcinoma cell lines. We observed that both gene and protein expression of SHP1 were negative in 8 of 10 gastric cancer cell li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…We previously reported that expression of SHP-1 is mostly attenuated or abolished in gastric cancer cell lines which are governed by epigenetic mechanism [ 8 ]. Sun et al showed that mRNA expression of SHP-1 is highest in normal gastric tissues, followed by intestinal metaplasia, dysplasia, and lowest in gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously reported that expression of SHP-1 is mostly attenuated or abolished in gastric cancer cell lines which are governed by epigenetic mechanism [ 8 ]. Sun et al showed that mRNA expression of SHP-1 is highest in normal gastric tissues, followed by intestinal metaplasia, dysplasia, and lowest in gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that the protein and messenger RNA (mRNA) expression of SHP-1 is negative or minimal in various gastric cancer cell lines, which are mainly governed by CpG island promoter hypermethylation. Reinforced SHP-1 expression in gastric cancer cells effectively inhibits STAT3 activity and its target genes such as cyclin D1, matrix metalloproteinases-9 (MMP-9), vascular endothelial growth factor-1 (VEGF-1), and survivin [ 8 ]. Here, we report on the anti-EMT effect of ATO in gastric cancer cells by demonstrating dephosphorylation of JAK2/STAT3 and modulation of EMT markers including Snail1 and E-cadherin by ATO, and suggest that SHP-1 might be an important mediator for inactivation of the JAK2/STAT3 signaling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…However, concerning the expression of SHP-1 in stomach tissue, data are very lacking. We have previously investigated promoter hypermethylation and gene expression of SHP-1 in most of gastric cancer cells and functional effects of SHP-1 on JAK2/STAT3 pathway [ 6 ]. Because protein or gene expression level of SHP-1 is very weak in most of stomach cancer tissues, SHP-1-induction strategy appears to be reasonable to effectively inhibit constitutive STAT3.…”
Section: Introductionmentioning
confidence: 99%
“…SHP-1 was initially classified as a tumor suppressor phosphatase [ 179 ] since its silencing, due to hypermethylation of CpG islands in the PTPN6 promoter region, is frequently associated with a poor prognosis and worse outcome in different types of cancers [ 180 , 181 , 182 , 183 , 184 , 185 , 186 , 187 , 188 , 189 ]. Indeed, several studies underlined that this enzyme controls cell cycle progression by impairing PDGF and insulin receptor signaling [ 190 , 191 ].…”
Section: Role Of Ptps In Immune Melanoma Cell Infiltratementioning
confidence: 99%